Funkcja stabilizacyjna Konkordatu polskiego z 1993 r. wobec Kościoła katolickiego i innych związków wyznaniowych - Borecki, Paweł (Studia Prawa Publicznego, 2019)
The stabilising function is one of the main intended functions of the concordats. It consists in striving to ensure the immutability (stability) of legal norms resulting from the provisions of this type of treaties, and consequently to ensure the relative immutability of legal (and factual) states created or shaped under the concordat government. The Concordat petrifies a model of relations between the state and the Catholic Church. In fact, it protects a certain system of social, political and, to some extent, economic relations. This function in the Polish legal system is guaranteed in particular by the provisions of the Constitution of the Republic of Poland of 1997 (Article 25(3) and (5)) and the provisions of the 1969 Vienna Convention on the Law of Treaties. The Concordat of 1993 is therefore legally difficult to denounce. The Treaty provides a differentiated implementation of the stabilising function. Individual norms of this act, to varying degrees, implement its stabilising function. It seems that it is most fully implemented through detailed standards of an absolutely binding nature. The second category of concordat norms from the point of view of the implementation of the stabilising function should include norms whose implementation depends on a later agreement between the Church and the relevant state authorities. As a third category, one should mention regulations which, when formulating legal norms, refer to canon law or state law. The last group consists of norms, the implementation of which depends, in fact, on a unilateral decision of the state authorities. The degree to which a stabilising function is carried out by the provisions of the Concordat also depends on the level of detail. The Concordat of 1993 is not a full concordat and therefore provides limited stability in the financial and property affairs of the Catholic Church and clergy. In practice, however, the 1993 Treaty, combined with the political strength of the Church, has ensured relatively good legal stability for the Church, although it has not yet been fully implemented and has seen some obvious violations. In many aspects, however, there has been an improvement in the legal position of the Church.